CONFLITS ARMES, INTEGRATION ET DEVELOPPEMENT DURABLE: Réflexion sur le rôle de l’ECOSOCC et des OSC en Afrique centrale - Tshibwabwa Kuditshini, Jacques (Centro de Estudios Avanzados, 2018)
Given its uncountable natural resources, Central Africa appearstoday as one of the most important subregions in the African integrationprocess. Unluckily, this part of the continent has fallen prey to economicand political instability due to the recurrent armed conflicts that turnany attempt to integration and sustainable development precarious.This is an area permanently in tension and demands strategiesand stability mechanisms as well as coexistence beyond frontiers, beforeattempting political integration. Among those in charge of contributingto such stability are organizations such as the OSC (Civil SocietyOrganization) and the ECOSOCC (African Cultural Social andEconomic Council).This article aims to confront the objectives of the ECOSOCC withthe complex sociopolitical dynamics in the subregion of Central Africa,based on two main points: one of them analyzes the African integrationissue in the light of the recent sociopolitical and economic evolutionand the other considers the chances of success of the ECOSOCC andOSC in the integration process of the mentioned subregion.